Association of Age at Menopause With Incident Heart Failure: A Prospective Cohort Study and Meta‐Analysis. Issue 8 (August 2016) - Appiah, Duke; Schreiner, Pamela J.; Demerath, Ellen W.; Loehr, Laura R.; Chang, Patricia P.; Folsom, Aaron R.
Abstract : Background: Early age (<45 years) at menopause has been postulated to be associated with increased cardiovascular disease risk; however, evidence of its relation with heart failure (HF) incidence is limited. We examined whether age at menopause is associated inversely with HF incidence in the Atherosclerosis Risk In Communities (ARIC) study and summarized all existing data in a meta‐analysis. Methods and Results: In ARIC, data were obtained from 5629 postmenopausal women (mean age 56 years, 26% with bilateral oophorectomy) without HF. During a median follow‐up of 21.4 years, 965 incident HF events occurred. In a Cox regression model adjusted for reproductive health and HF risk factors, the hazard ratios for incident HF across categories of age at menopause (<45, 45–49, 50–54, and ≥55 years) were 1.32, 1.17, 1.00 (referent), and 1.12, respectively. Compared with women with later onset of menopause (aged ≥45 years), those with early menopause had elevated HF risk (hazard ratio 1.20, 95% CI 1.01–1.43). For the meta‐analysis, we searched Medline and Embase for articles published through December 2015 that prospectively evaluated age at menopause and HF risk. Summarized estimates from the 3 included studies (3568 events) showed higher HF risk among women with early menopause compared with those with later menopause (hazard ratio 1.33, 95% CI 1.15–1.53). Conclusions: These results provided evidence that early age at menopause is associated with a modestly greater risk of HF. Identification of women with early menopause offers a window of opportunity to implement interventions that will improve overall cardiovascular health during the postmenopausal years.